2020
DOI: 10.3389/fcimb.2020.00282
|View full text |Cite
|
Sign up to set email alerts
|

RcsAB and Fur Coregulate the Iron-Acquisition System via entC in Klebsiella pneumoniae NTUH-K2044 in Response to Iron Availability

Abstract: The iron acquisition system is an essential virulence factor for human infection and is under tight regulatory control in a variety of pathogens. Ferric-uptake regulator (Fur) is one of Fe 2+-responsive transcription factor that maintains iron homeostasis, and the regulator of capsule synthesis (Rcs) is known to regulate exopolysaccharide biosynthesis. We speculate the Rcs may involve in iron-acquisition given the identified regulator box in the upstream of entC that participated in the biosynthesis of enterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Interestingly, the Rcs system is involved in production of colanic acid capsule, thus, an interrelation between O antigen polymerization in LPS and colanic acid in the stress response is plausible as denotes the fact that bacteria without O antigen in LPS overproduces colanic acid ( 64 ). Also, the relation between Rcs and regulation of iron related genes is observed in the RNAseq analysis upon expression of the RcsB M88A variant and it has been demonstrated in a recent publication that the heterocomplex RcsB-RcsA together with Fur co-regulate iron-acquisition via entC in Klebsiella pneumoniae ( 65 ). This previously unknown aspect of RcsB over iron regulation highlights the crucial role that iron plays in bacterial physiology in basal and altered conditions, not in vain, iron regulation is also under control of the stress response sigma factor RpoS (σ S ) to prevent oxidative stress ( 66 ).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the Rcs system is involved in production of colanic acid capsule, thus, an interrelation between O antigen polymerization in LPS and colanic acid in the stress response is plausible as denotes the fact that bacteria without O antigen in LPS overproduces colanic acid ( 64 ). Also, the relation between Rcs and regulation of iron related genes is observed in the RNAseq analysis upon expression of the RcsB M88A variant and it has been demonstrated in a recent publication that the heterocomplex RcsB-RcsA together with Fur co-regulate iron-acquisition via entC in Klebsiella pneumoniae ( 65 ). This previously unknown aspect of RcsB over iron regulation highlights the crucial role that iron plays in bacterial physiology in basal and altered conditions, not in vain, iron regulation is also under control of the stress response sigma factor RpoS (σ S ) to prevent oxidative stress ( 66 ).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a total of 14 pathogenic genes with significant differences in abundance were identified between the two groups. Among them, entA,entC, entF, fepC, fepG, and iucA were the major virulence factors related to iron uptake in K. pneumoniae (Yuan et al, 2020); the pilus regulatory gene fimK promotes the virulence of K. pneumoniae in murine pneumonia (Rosen et al, 2015;Liu et al, 2022); arcB may mediate resistance against host-derived antimicrobial peptides (Padilla et al, 2010); magA is associated with the virulent hypermucoviscous K. pneumoniae strains (Cubero et al, 2016). The relationship between these genes and the invasiveness of KPLA should be verified via further research.…”
Section: Discussionmentioning
confidence: 98%
“…The result that biofilm formation on abiotic surfaces was reduced following knockdown of the ykgK gene suggested that the ykgk gene played a role in biofilm formation. In K. pneumoniae, it is known that Type 1 and 3 fimbriae play an important role in the formation of biofilms [7,37,38]. After studying the ykgK gene, it was found that the phenotypes were related to biofilm formation, in addition to Type 1 and Type 3 fimbriae, as well as ECP fimbriae.…”
Section: Infection Of G Mellonella Larvaementioning
confidence: 99%
“…Current research on the virulence of K. pneumoniae has also attracted much attention. The known virulence factors of K. pneumoniae mainly include capsular polysaccharide (CPS), lipopolysaccharide, fimbriae, urease, biofilm formation‐related factors, and the iron capture system [2–7]. Bacterial biofilms are surface‐related aggregates embedded in extracellular polymer intermediates, which help bacteria resist external environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation